Pengaruh Servant Leadership dan Reward Terhadap Kinerja Karyawan Perusahaan PT General Indah Mustika - Fatimah Pohan (Forum Kerjasama Pendidikan Tinggi, 2021)
Quality control is very important to do to find out important aspects of the pace and sustainability of a company to keep operating, the importance of searching for information on the state and condition of a company both internally and externally, at this stage several tests are carried out on the data of an influence phenomenon. reward and leadership on employee performance on product sales using data testing methods and the relationship between each relationship between one variable and another, testing can be done using a statistical measurement and testing tool in the form of SPSS with 50 respondent data, the use of this testing tool will facilitate research in seeing the relationship of variables with accurate and fast results. The results of this study indicate that the effect of giving rewards to employees has a higher value of 4,468, while the servant leadership attitude has a value of 3,420, so that this value shows the effect of giving rewards to employees is greater to increase interest in better employee performance.